Comparison of Predictors of COVID-19 Vaccination Intention Between Healthcare Workers and Non-Healthcare Workers in China - Chi L; Zhao G; Chen N; Shen G; Huang K; Xia X; Chen Y; Liu J; Xu R; Chen Y; Dong W; Zheng J (Journal of Multidisciplinary Healthcare, 2021)
Lisha Chi,1,* Guojing Zhao,2,* Naiche Chen,3,* Guanghui Shen,4 Kai Huang,4 Xiaoyu Xia,1 Yijing Chen,1 Jian Liu,1 Ran Xu,5 Yanhan Chen,6 Weijie Dong,7 Jiexia Zheng8 1School of Pharmaceutical Science, Wenzhou Medical University, Wenzhou, People’s Republic of China; 2Institute of China Innovation and Entrepreneurship Education, Wenzhou Medical University, Wenzhou, People’s Republic of China; 3Renji College, Wenzhou Medical University, Wenzhou, People’s Republic of China; 4School of Mental Health, Wenzhou Medical University, Wenzhou, People’s Republic of China; 5Department of Natural Science, Affiliated School of Wenzhou University Town, Wenzhou, People’s Republic of China; 6School of Stomatology, Wenzhou Medical University, Wenzhou, People’s Republic of China; 7The 1th School of Medicine, Wenzhou Medical University, Wenzhou, People’s Republic of China; 8Department of Student Affairs, Wenzhou Medical University, Wenzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiexia ZhengDepartment of Student Affairs, Wenzhou Medical University, Wenzhou, Zhejiang Province, People’s Republic of ChinaEmail zhengjiexia2021@163.comBackground: Vaccination is an effective strategy to mitigate the spread of COVID-19. This study aimed to compare predictors of vaccination intention between healthcare workers (HCWs) and non-healthcare workers (non-HCWs) in China.Methods: A web-based cross-sectional survey was conducted among HCWs and non-HCWs. Several bivariate analysis techniques, eg, crosstab with Chi-square, independent t-test and single factor ANOVA, were performed to analyze the correlation. After that, a series of multivariate binary regressions were employed to determine predictors of vaccination intention.Results: Intention was closely and significantly related with gender, perceived vaccination knowledge, perceived importance and effectiveness of vaccine to prevent COVID-19. HCWs and non-HCWs were heterogeneous, since vaccination intention, perceived knowledge, and attitudes (eg, importance, severity, risk) toward COVID-19 or vaccine had statistically significant difference between the two groups. With comparison of predictors of vaccination intention, for HCWs, demographic factors were the major predictors of COVID-19 vaccination intention. Female HCWs and HCWs with a Master’s or higher degree were more hesitant about vaccination (P = 0.01 and P < 0.001, respectively), while HCWs had greater vaccination intention as their age increased (P = 0.02). For non-HCWs, perceived vaccination knowledge was the major predictor of COVID-19 vaccination intention (P < 0.001). Additionally, perceived importance and effectiveness of vaccine were predictors for both HCWs and non-HCWs.Conclusion: Vaccination intention of HCWs was greater than that of non-HCWs in China. Measures should be taken to improve the vaccination rate based on the predictors of vaccination intention identified in this study. For HCWs, especially those with a high level of education or who were females, the safety and effectiveness of vaccines in use may reinforce their vaccination intention. For non-HCWs, popularization of general medical knowledge, including of vaccine-preventable diseases, may increase their vaccination intention.Keywords: COVID-19 vaccine, intention, predictor, HCWs, non-HCWs